Pattern of Food Cravings in Pregnant Women Receiving Antenatal Care in a Community Setting - Bashar, Mohammad Abul; Yesmin, Farida; Rafa, Shaila Sharmin; Rahman, Rahnuma (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Food cravings are a sudden desire to eat certain types of foods during pregnancy. Worldwide, it is a common phenomenon. Objectives: To find out the pattern of craving foods and examine to what extent the craving desires were fulfilled. Methods: This cross-sectional study was conducted among 150 pregnant women in a community setting. Data were collected during January to March 2020 by face-to-face interview with a semi-structured questionnaire. Sample women were selected purposively. Results: Mean age of the sample women was 23.59 (±4.36) years. 78% (117) of the respondents had cravings for one or more foods. Of them, 29.9% women had craved for sour fruits and 32.5% women had craved for milk-based sweets. Besides, 15.4%, 17.1% and 20.5% women had craved yogurt with misti, rice-milk-banana mixed and pickles respectively. Another 1.7% women had craved for non-food substance burnt clay. 23.9% craving desires was due to inhibiting nausea and 57.3% had no explanation. 70.9% craving desires was fulfilled. The proportion of fulfillment of craving desires was 100% in higher income families (p<.001). In joint families, 78.9% craving desires was fulfilled. It was 56.1% in the nuclear family (p=.009). In the first pregnancy, 81.5% craving desires was fulfilled (p=.003). Conclusion: Common foods for pregnancy cravings were sweets, sour fruits and pickles. Craving desires was fulfilled more in high income families, joint families and in first pregnancy. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 55-58